A Comparative Transcriptome Analysis of Human and Porcine Choroid Plexus Cells in Response to Streptococcus suis Serotype 2 Infection Points to a Role of Hypoxia - Lauer, Alexa N.; Scholtysik, Rene; Beineke, Andreas; Baums, Christoph Georg; Klose, Kristin; Valentin-Weigand, Peter; Ishikawa, Hiroshi; Schroten, Horst; Klein-Hitpass, Ludger; Schwerk, Christian (Frontiers in Cellular and Infection Microbiology, 2021)
Streptococcus suis (S. suis) is an important opportunistic pathogen, which can cause septicemia and meningitis in pigs and humans. Previous in vivo observations in S. suis-infected pigs revealed lesions at the choroid plexus (CP). In vitro experiments with primary porcine CP epithelial cells (PCPEC) and human CP epithelial papilloma (HIBCPP) cells demonstrated that S. suis can invade and traverse the CP epithelium, and that the CP contributes to the inflammatory response via cytokine expression. Here, next generation sequencing (RNA-seq) was used to compare global transcriptome profiles of PCPEC and HIBCPP cells challenged with S. suis serotype (ST) 2 infected in vitro, and of pigs infected in vivo. Identified differentially expressed genes (DEGs) were, amongst others, involved in inflammatory responses and hypoxia. The RNA-seq data were validated via quantitative PCR of selected DEGs. Employing Gene Set Enrichment Analysis (GSEA), 18, 28, and 21 enriched hallmark gene sets (GSs) were identified for infected HIBCPP cells, PCPEC, and in the CP of pigs suffering from S. suis ST2 meningitis, respectively, of which 8 GSs overlapped between the three different sample sets. The majority of these GSs are involved in cellular signaling and pathways, immune response, and development, including inflammatory response and hypoxia. In contrast, suppressed GSs observed during in vitro and in vivo S. suis ST2 infections included those, which were involved in cellular proliferation and metabolic processes. This study suggests that similar cellular processes occur in infected human and porcine CP epithelial cells, especially in terms of inflammatory response.